Bulletin 92 The Feldspars of the New England and North Appalachian States - A. S. Watts (The National Institute for Occupational Safety and Health (NIOSH), 1916)
The Bureau of Mines has been conducting an investigation of the feldspar resources of the New England and North Appalachian States with a view to greater efficiency and economy in their utilization. Such an investigation was deemed necessary, not only because of the continued and increasing consumption of these minerals, but especially because of the demand for better technical control of the raw materials that are used by the white-ware industries of the United States. Most manufacturers of white pottery wares have only a limited knowledge of the origin, mode of occurrence, and methods of mining and preparation of the materials that they use. Heretofore, owing to a belief that the supply of raw material was unlimited, the manufacturer had concerned himself chiefly with the solution of the problems of manufacture. Within the past few years, however, it has been found that difficulties arise in manufacture which can be traced beyond the manufacturing process and are believed to be due to a need of better control of the materials used. Furthermore, as competition becomes more severe, more attention must be paid to selection of materials in order to minimize consumption and also to avoid unnecessary expense for transportation of material. Doubtless the lack of interest as regards these details has arisen from the fact that in the past a considerable proportion of the whiteware ingredients has been imported and the manufacturer has been forced to rely on the samples submitted and the general uniformity of the source of supply to insure against variation of the material. An extra precaution arising from this lack of definite knowledge still prevails in the common practice of never depending on one source of supply for anyone ingredient. Often the products of three or more producers are blended so that if anyone shall vary without warning the variation arising from its use will not be sufficient to ruin the ware.